A novel variation of GDF3 in Chinese Han children with a broad phenotypic spectrum of non-syndromic CHDs. (5th November 2014) - Xiao, Jianmin; Kang, Guanyang; Wang, Jing; Li, Tengyan; Chen, Jiuhao; Wang, Jieyin; Li, Wei; Wang, Binbin
Abstract Background The GDF3 gene plays a fundamental role in embryonic morphogenesis. Recent studies have indicated that GDF3 plays a previously unrecognised role in cardiovascular system development. Non-syndromic CHDs might be a clinically isolated manifestation of GDF3 mutations. The purpose of the present study was to identify potential pathological mutations in the GDF3 gene in Chinese children with non-syndromic CHDs, and to gain insight into the aetiology of non-syndromic CHDs. Methods A total of 200 non-syndromic CHDs patients and 202 normal control patients were sampled. There were two exons of the human GDF3 gene amplified using polymerase chain reaction. The polymerase chain reaction products were purified and directly sequenced. Results One missense mutation (c.C635T, p.Ser212 Leu, phenotype: isolated muscular ventricular septal defect) was found that has not been reported previously. Conclusions To the best of our knowledge, this is the first study to investigate the role of the GDF3 gene in non-syndromic CHDs. Our results expand the spectrum of mutations associated with CHDs and first suggest the potentially disease-related GDF3 gene variant in the pathogenesis of CHDs.